Testicular torsion in undescended testis: A persistent challenge - Sahbi Naouar; Salem Braiek; Rafik El Kamel (Asian Journal of Urology)
Objective: To evaluate the management and outcomes of patients who presented with torsion of an undescended testis and review the reported series in the literature. Methods: The case records of 13 patients operated for testicular torsion involving undescended testis were retrospectively reviewed. The medical records included age at presentation, medical history, physical examination, operative findings and the results of follow-up. The diagnosis of torsion of undescended testis was made clinically and confirmed by inguinal exploration. Results: In six cases the testis was preserved and orchiopexy was performed, while in seven cases orchidectomy was performed due to testicular gangrene in six patients and testicular tumor discovered peroperatively in one case. Mean duration of symptoms at time of surgery in the orchiopexy group was 6.5 h and in the orchidectomy group was 21.2 h. From six patients treated by orchiopexy, two patients suffered from testicular atrophy at a mean of 24 months. Conclusion: Testicular torsion in undescended testis is still diagnosed with delay which may affect testicular salvage. The importance of examination of external genital organs is highlighted which should be routinely included by emergency physicians in physical examination for abdominal or groin pain.